Perceptions of the Promotion of Entrepreneurial Competence in the Education System Among Education Professionals - Andrea Gracia-Zomeño; Eduardo García-Toledano; Ramón García-Perales; Ascensión Palomares-Ruiz (Education Sciences, 2025)
Teacher entrepreneurship is a fundamental aspect of today’s education. Entrepreneurial Competence (EC), as established in Organic Law 3/2020, which amends Organic Law 2/2006, on Education, and reinforced by Law 14/2013, on Support for Entrepreneurs and Their Internationalization, is key to preparing students for the challenges of the 21st century. This study follows a quantitative observational design, with data collected through a questionnaire administered to over 600 education professionals, structured into three blocks and fourteen dimensions. The research is divided into three parts, corresponding to the three blocks of the questionnaire. This article focuses on the first block, which aims to evaluate teachers’ assessment of EC and to analyse their perception of the most accessible and effective options for adequately developing this competence in educational centres. Results show that all participant groups generally rated EC highly, but perceptions differ based on gender, age, and training. Teachers with EC training express greater confidence, while those without training report more challenges. School leaders rate EC more favourably, likely due to their involvement in institutional policies. The main obstacles identified are insufficient teacher training and inadequate resources. The study emphasises the importance of enhancing teacher training and adopting active methodologies to integrate entrepreneurship into education. It also underscores practical implications for educational policy, emphasising curriculum reforms, resource allocation, and stronger school–business collaboration to foster an entrepreneurial mindset.